Discursive Scenographies and Narrative Regimes of Trump’s Leadership in African News Media - Léon Martin Mbembo Likongo (CV. Literasi Indonesia, 2026)
This article examines how African news media construct Donald Trump’s leadership during the first year of his renewed presidency (20 January 2025–20 January 2026). Drawing on a qualitative, multi-site design, the study analyzes a multilingual corpus of nine African outlets using a two-track framework that combines discursive scenography and narrative regime analysis. The findings identify six recurrent scenographies—Executive Mediation, Sovereign Restoration, Conditional Supervision, Strategic Deterrence, Institutional Negotiation, and Ambivalent Disruption—and six narrative regimes, including Escalation–Resolution and Security–Protection. Results show that leadership legitimacy is stabilized when enunciative centrality aligns with coherent narrative closure and becomes conditional when monitoring and uncertain aftermath dominate follow-up coverage. The study concludes that African media do not passively reproduce Western frames but actively recontextualize global leadership within mineral geopolitics, sovereignty concerns, and security priorities. By articulating scenography and narrative regime, the article advances a transferable framework for analyzing mediated legitimacy in multipolar communication environments.